Opaque Proliferation: The Historiography of Australia's Cold War Nuclear Weapons Option - Auton, Luke (History compass, 2013)
This article looks at Australia's Cold War Interest in Manufacturing or Otherwise Acquiring nuclear weapons. It will examine the development of the historiography and highlight views from the field, including perspectives from disciplines other than history. Its key objective will be to show how these views have informed contemporary observations about nuclear issues in Australia, and question why it is that discussion of such issues invites allusions to everything from previous nuclear weapon ‘ambitions’, to a genuine Australian nuclear weapon programme. This paper will contend that such allusions reflect divergent views in the field, as well as the poor collective capacity of the historiography for depicting the complexity - and denoting the dynamics - of proliferation. The final goal of this paper will be to survey how the historiography is evolving to increasingly bring together the various approaches and judgments on Australia's Cold War nuclear weapons option.